Methods of increasing the efficiency of the worm gear - Melnikov Pavel; Schegoleva Svetlana (MATEC Web of Conferences, 2019)
This article describes the geometric features of the worm gear, the principle of operation and the theoretical basis for calculating the efficiency. A number of research works aimed at the development of new advanced techniques, both production and use of worm gear were analyzed. Based on the analyzed techniques, one was chosen and confirmed experimentally. Based on the performed researches and experiments, recommendations were developed to improve the efficiency of the worm gear type 2H-63.